Rapid deployment bioprostesis for aortic valve stenosis: single center short and long-term outcomes. (3rd October 2022) - Ferreira, R; Velho, T; Sena, A; Goncalves, J; Junqueira, N; Pereira, R; Almeida, A; Pinto, F; Nobre, A
Abstract: Background: Despite recent advances, surgical aortic valve replacement (SAVR) remains the gold standard for most of the patients with aortic valve stenosis. The ageing population, with increased comorbidities and the rising of minimally invasive techniques, led to the development of new prosthetic devices of easier and faster implantation. Purpose: This study aimed to analyse short and long-term outcomes of SAVR with rapid-deployment (RD) aortic bioprosthesis for isolated aortic valve stenosis Method: Singe center, retrospective longitudinal cohort study of patients with isolated aortic valve stenosis who underwent elective aortic valve replacement using RD devices between 2014 and December 2021. Continuous variables are presented with median (IQR) and were analyzed using Mann-Whitney test. Categorical variables are presented in percentage or frequency and were analyzed using chi-square test. Kaplan-Meyer survival curve was constructed base on collected data from national registry. Results: A RD device was implanted in 358 patients with a median age of 75, 8 years and Euroscore II of 2, 3. Median cross clamp and extracorporeal circulation time were 27, 4 and 36, 7 min, respectively. No significant paravalvular leaks. Intensive care unit (ICU) length of stay was 3 days with acute renal lesion (any stage-53, 2%; Dialysis-2, 5%), need for hemodynamic support (63, 1%) and new onset atrial fibrillation (33, 6%) being the most frequent post-operative complications. Stroke occurred in 0, 6% of cases and mortality was 1, 1%. Pacemaker implementation rate of 11%. The mean follow-up time was 6, 7 years with 90% 5-years survival rate. Mean gradients of 11, 2±4, 8 mmHg at 6 months Conclusion: Surgical treatment of aortic valve stenosis using RD devices is safe, with a low mortality rate. ICU length of stay and hospital length of stay are reduced. Follow-up shows an excellent long-term survival and hemodynamic performance. Funding Acknowledgement: Type of funding sources: None.